Flame retardant ceramic fiber felt and production process thereof

By grafting polymer chains on the surface of ceramic fibers and depositing nanosilicon dioxide, the problem of poor dispersion of ceramic fiber felt in wet molding is solved, and its flame retardant and mechanical properties are significantly improved.

CN118721376BActive Publication Date: 2025-01-03INNER MONGOLIA HONGYANG HIGH TEMPERATURE THERMAL INSULATION MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411233263.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2025-01-03
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

Ceramic fiber felt is difficult to disperse and decompose evenly during wet forming process, resulting in uneven structure of the fiber felt after forming, poor flame retardancy and mechanical properties.

Method used

By grafting hydrophilic-hydrophobic polymer chains on the surface of quartz fibers and depositing nanosilicon dioxide, the flame retardant is modified to improve its dispersion and immobilization on ceramic fibers, amination reaction and ultrasonic dispersion technology are used. , forming a uniform flame retardant ceramic fiber felt.

Benefits of technology

The flame retardant and mechanical properties of ceramic fiber felt are improved, ensuring uniform dispersion of flame retardant and nanosilicon dioxide on the fiber surface, and enhancing its flame retardant ability and physical strength.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a flame-retardant ceramic fiber felt and a production process thereof, belonging to the technical field of ceramic fiber felts. The invention comprises the following steps: adding an aminated flame retardant, urea and dicyandiamide to a quartz fiber dispersion liquid, reacting the mixture, mixing the mixture with a tetramethyl orthosilicate methanol solution, adding a 2-bromoethylamine hydrobromide ethanol solution, adjusting the pH value with ammonia water, filtering and washing to obtain a pre-treated slurry, filtering the pre-treated slurry at a low speed with a small-aperture filter plate in a mold, pressurizing to obtain a fiber wet blank, and drying the fiber wet blank to obtain a flame-retardant ceramic fiber felt; in the flame-retardant ceramic fiber felt prepared by the production process of the invention, a flame retardant and nano silicon dioxide are uniformly dispersed on the surface of the ceramic fiber, and a hydrophilic-hydrophobic polymer chain is grafted on the surface of the ceramic fiber to improve the dispersibility of the ceramic fiber in the aqueous solution, thereby improving the dispersion degree of the flame retardant and the nano silicon dioxide on the surface of the ceramic fiber, so that the flame-retardant ceramic fiber felt has good flame retardancy and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic fiber felt, and in particular relates to a flame-retardant ceramic fiber felt and a production process thereof. Background Art

[0002] The preparation and molding technology of ceramic fiber felt mostly adopts dry molding process, namely bonding and pressing method and needle punching molding method, but the ceramic fiber felt obtained by dry molding is mostly used in construction and industrial fields, and the fiber felt has poor structural uniformity, low flame retardancy and mechanical properties. Compared with dry molding, wet molding has process controllability, and the prepared fiber felt exhibits better flame retardancy and mechanical properties.

[0003] At present, the preparation process of ceramic fiber felt is mostly a wet molding process, that is, short chopped fibers are evenly dispersed in a solvent to form a slurry, and then cured by the above-mentioned physical or chemical methods to obtain a fiber felt. However, since ceramic fibers do not have hydrophilic groups in their chemical structure and do not have capillary structures in their physical structure, it is difficult to suspend and disperse them evenly and stably in water. And because there is charge distribution on the surface of ceramic fibers, the fibers attract and repel each other in the slurry, causing the fibers to flocculate. This problem of difficult dispersion and easy aggregation will greatly reduce the various properties of the formed fiber felt.

[0004] Patent CN113683387A discloses a hydrophobic flame-retardant silica aerogel ceramic fiber felt and a preparation method thereof, wherein water glass and a flame retardant are mixed, impregnated into the ceramic fiber felt, and dried to obtain a hydrophobic flame-retardant silica aerogel ceramic fiber felt; this solution is more dependent on the degree of dispersion of the flame retardant in the water glass during the impregnation process, and the precipitation effect caused by gravity during the impregnation will also cause the silica aerogel and the flame retardant to be unevenly dispersed, affecting the performance of the fiber felt. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of how to improve the dispersibility of modified substances in ceramic fiber felt so as to improve the mechanical ability and flame retardancy of the ceramic fiber felt, and to provide a flame retardant ceramic fiber felt and a production process thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A production process of flame-retardant ceramic fiber felt comprises the following steps:

[0008] Step 1: Add aminated flame retardant, urea and dicyandiamide to the quartz fiber dispersion, stir and react at 35-45° C. for 12-24 hours to obtain a flame retardant quartz fiber dispersion.

[0009] Step 2: Dissolve tetramethyl orthosilicate in methanol in a beaker, mix with the flame-retardant quartz fiber dispersion, add 10-12wt% 2-bromoethylamine hydrobromide ethanol solution, adjust the pH value to 6.5-7 with ammonia water, stir the reaction at 50-55°C for 6-8h, filter the solid, and wash the precipitate with ethanol and deionized water in turn to obtain a pretreated slurry.

[0010] Step 3: Filter the pretreated slurry in a mold at a low speed using a small-pore filter plate to form a fiber block, and then apply a pressure of 1-1.1 MPa to the fiber block to obtain a fiber wet blank. Dry the fiber wet blank in an oven at 60-65°C for 12-16 hours to obtain a flame-retardant ceramic fiber felt.

[0011] Furthermore, in step 1, the mass ratio of the quartz fiber dispersion, the aminated flame retardant, the urea and the dicyandiamide is 200-250:15-20:3-5:3-5.

[0012] Furthermore, in step 2, the dosage ratio of tetramethyl orthosilicate, methanol, flame retardant quartz fiber dispersion, and 2-bromoethylamine hydrobromide ethanol solution is 4-5 mL: 20-30 mL: 200-250 g: 35-50 mL.

[0013] Furthermore, the quartz fiber dispersion in step 1 is prepared by the following steps:

[0014] The pulped quartz fiber was mixed with distilled water, polymer chains were added, the pH value of the solution was adjusted to 3-4 with dilute sulfuric acid after stirring and dispersion, ultrasonic dispersion was performed for 30-40 minutes, the pH value was adjusted to 6.5-7 with sodium hydroxide solution, and ultrasonic dispersion was continued for 30-40 minutes to obtain a quartz fiber dispersion.

[0015] Furthermore, the usage ratio of quartz fiber, distilled water and polymer chain is 100-130 g: 1-1.5 L: 15-20 g.

[0016] Furthermore, the aminated flame retardant in step 1 is prepared by the following steps:

[0017] Dissolve polyethyleneimine and phosphorous acid in deionized water in a beaker, drop formaldehyde into the beaker, react at 80-90°C for 2-3 hours, adjust the pH value to 5-6 with ammonia water, remove the solvent by rotary evaporation, wash the solid with ethanol, and dry at 60-70°C for 12-16 hours to obtain an aminated flame retardant.

[0018] Furthermore, the usage ratio of polyethyleneimine, phosphorous acid, deionized water and formaldehyde is 10-15g:20-25g:100-120mL:20-25g.

[0019] Further, the polymer chain is prepared by the following steps:

[0020] In a flask, 2-(dimethylamino)ethyl methacrylate and 2-(diisopropylamino)ethyl methacrylate are mixed in tetrahydrofuran, and azobisisobutyronitrile is added to initiate polymerization. The reaction is carried out at 65-75°C for 20-24 hours. After cooling, the solution is precipitated with petroleum ether. The obtained solid is vacuum dried at 40-50°C for 36-48 hours to obtain a polymer chain.

[0021] Furthermore, the usage ratio of 2-(dimethylamino)ethyl methacrylate, 2-(diisopropylamino)ethyl methacrylate, tetrahydrofuran and azobisisobutyronitrile is 2-3 g: 3-5 g: 80-100 mL: 6-8 mg.

[0022] Beneficial effects of the present invention:

[0023] In the flame-retardant ceramic fiber felt prepared by the production process of the present invention, the flame retardant and nano-silicon dioxide are evenly dispersed on the surface of the ceramic fiber. By grafting hydrophilic-hydrophobic polymer chains on the surface of the ceramic fiber, the dispersibility of the ceramic fiber in the aqueous solution is improved, thereby improving the dispersion degree of the flame retardant and nano-silicon dioxide on the surface of the ceramic fiber. The obtained flame-retardant ceramic fiber felt has good flame retardancy and mechanical properties.

[0024] The production process of the present invention modifies the flame retardant by amination, so that the amine group in the flame retardant reacts and grafts with the polymer chain on the surface of the ceramic fiber, thereby fixing and dispersing the flame retardant on the surface of the ceramic fiber, and depositing nano-silicon dioxide on the surface of the polymer chain so that the nano-silicon dioxide is uniformly deposited on the ceramic fiber, thereby improving the mechanical properties of the flame-retardant ceramic fiber felt, and at the same time making the nano-silicon dioxide attached to the surface of the flame retardant. After extrusion drying and molding, the flame retardant can form a protective layer on the surface of the nano-silicon dioxide more quickly, thereby improving the flame retardant ability of the flame-retardant ceramic fiber felt. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Embodiment 1: A production process of a flame retardant ceramic fiber felt, comprising the following steps:

[0027] Step 1: In a flask, mix 20 g of 2-(dimethylamino)ethyl methacrylate and 30 g of 2-(diisopropylamino)ethyl methacrylate in 800 mL of tetrahydrofuran, add 60 mg of azobisisobutyronitrile to initiate polymerization, react at 65°C for 20 h, cool and precipitate the solution with petroleum ether, and dry the obtained solid in vacuum at 40°C for 36 h to obtain a polymer chain.

[0028] Step 2: Use a high-speed pulper to chop the quartz fiber into short pieces at a speed of 2800 r / min. Mix 200 g of the pulped quartz fiber with 2 L of distilled water, add 30 g of polymer chain, stir and disperse, adjust the pH value of the solution to 3 with 0.1 M dilute sulfuric acid, ultrasonically disperse for 30 min, adjust the pH value to 6.5 with 0.1 M sodium hydroxide solution, and continue ultrasonically dispersing for 30 min to obtain a quartz fiber dispersion.

[0029] Step 3: Dissolve 10 g of polyethyleneimine and 20 g of phosphorous acid in 100 mL of deionized water in a beaker, drop 20 g of formaldehyde into the beaker, react at 80° C. for 2 h, adjust the pH value to 5 with ammonia water, remove the solvent by rotary evaporation, wash the solid with ethanol, and dry at 60° C. for 12 h to obtain an aminated flame retardant.

[0030] Step 4: Add 15 g of aminated flame retardant, 3 g of urea and 3 g of dicyandiamide to 200 g of quartz fiber dispersion, stir and react at 35° C. for 12 h to obtain a flame-retardant quartz fiber dispersion.

[0031] Step 5. Dissolve 4 mL of tetramethyl orthosilicate in 20 mL of methanol in a beaker, mix with 200 g of flame-retardant quartz fiber dispersion, add 35 mL of 10 wt% 2-bromoethylamine hydrobromide ethanol solution, adjust the pH to 6.5 with ammonia water, stir the reaction at 50 ° C for 6 h, filter the solid, and wash the precipitate with ethanol and deionized water in turn to obtain a pretreated slurry.

[0032] Step six: filter the pretreated slurry in a mold at a low speed using a small-pore filter plate to form a fiber block, and then apply a pressure of 1 MPa to the fiber block to obtain a fiber wet blank. Dry the fiber wet blank in an oven at 60° C. for 12 hours to obtain a flame-retardant ceramic fiber felt.

[0033] Embodiment 2: A production process of a flame retardant ceramic fiber felt, comprising the following steps:

[0034] Step 1: Mix 25 g of 2-(dimethylamino)ethyl methacrylate and 40 g of 2-(diisopropylamino)ethyl methacrylate in 900 mL of tetrahydrofuran in a flask, add 70 mg of azobisisobutyronitrile to initiate polymerization, react at 70°C for 22 hours, cool and precipitate the solution with petroleum ether, and dry the obtained solid in vacuum at 45°C for 42 hours to obtain a polymer chain.

[0035] Step 2: Use a high-speed pulper to chop the quartz fiber into short pieces at a speed of 2900 r / min. Mix 230 g of the pulped quartz fiber with 2.5 L of distilled water, add 35 g of polymer chain, stir and disperse, adjust the pH value of the solution to 3.5 with 0.1 M dilute sulfuric acid, ultrasonically disperse for 35 minutes, adjust the pH value to 6.7 with 0.1 M sodium hydroxide solution, and continue ultrasonically dispersing for 35 minutes to obtain a quartz fiber dispersion.

[0036] Step 3: Dissolve 12.5 g of polyethyleneimine and 22.5 g of phosphorous acid in 110 mL of deionized water in a beaker, drop 22.5 g of formaldehyde into the beaker, react at 85° C. for 2.5 h, adjust the pH value to 5.5 with ammonia water, remove the solvent by rotary evaporation, wash the solid with ethanol, and dry at 65° C. for 14 h to obtain an aminated flame retardant.

[0037] Step 4: Add 17.5 g of aminated flame retardant, 4 g of urea and 4 g of dicyandiamide to 225 g of quartz fiber dispersion, stir and react at 40° C. for 18 h to obtain a flame-retardant quartz fiber dispersion.

[0038] Step 5. Dissolve 4.5 mL of tetramethyl orthosilicate in 25 mL of methanol in a beaker, mix with 225 g of flame-retardant quartz fiber dispersion, add 40 mL of 11 wt% 2-bromoethylamine hydrobromide ethanol solution, adjust the pH to 6.7 with ammonia water, stir the reaction at 53 ° C for 7 h, filter the solid, and wash the precipitate with ethanol and deionized water in turn to obtain a pretreated slurry.

[0039] Step six: filter the pretreated slurry in a mold at a low speed using a small-pore filter plate to form a fiber block, and then apply a pressure of 1.05 MPa to the fiber block to obtain a fiber wet blank. Dry the fiber wet blank in an oven at 62.5°C for 14 hours to obtain a flame-retardant ceramic fiber felt.

[0040] Embodiment 3: A production process of a flame retardant ceramic fiber felt, comprising the following steps:

[0041] Step 1: In a flask, mix 30 g of 2-(dimethylamino)ethyl methacrylate and 50 g of 2-(diisopropylamino)ethyl methacrylate in 1000 mL of tetrahydrofuran, add 80 mg of azobisisobutyronitrile to initiate polymerization, react at 75°C for 24 hours, cool and precipitate the solution with petroleum ether, and dry the obtained solid in vacuum at 50°C for 48 hours to obtain a polymer chain.

[0042] Step 2: Use a high-speed pulper to chop the quartz fiber into short pieces at a speed of 3000 r / min. Mix 260 g of the pulped quartz fiber with 3 L of distilled water, add 40 g of polymer chain, stir and disperse, adjust the pH value of the solution to 4 with 0.1 M dilute sulfuric acid, ultrasonically disperse for 40 min, adjust the pH value to 7 with 0.1 M sodium hydroxide solution, and continue ultrasonically dispersing for 40 min to obtain a quartz fiber dispersion.

[0043] The 2-(dimethylamino)ethyl methacrylate in the polymer chain is hydrophilic, and the 2-(diisopropylamino)ethyl methacrylate is hydrophobic. The polymer chain is dissolved in an acidic solution in a molecular manner. The hydrophobic 2-(diisopropylamino)ethyl methacrylate and the hydrophobic quartz fiber will have an adsorption effect, and the 2-(diisopropylamino)ethyl methacrylate will adhere to the surface of the quartz fiber. By adjusting the pH value to neutral, the 2-(dimethylamino)ethyl methacrylate and the 2-(diisopropylamino)ethyl methacrylate will undergo a grafting reaction, so that the hydrophilic group is grafted onto the surface of the quartz fiber, increasing the dispersibility of the quartz fiber in water.

[0044] Step 3: Dissolve 15 g of polyethyleneimine and 25 g of phosphorous acid in 120 mL of deionized water in a beaker, drop 25 g of formaldehyde into the beaker, react at 90° C. for 3 h, adjust the pH value to 6 with ammonia water, remove the solvent by rotary evaporation, wash the solid with ethanol, and dry at 70° C. for 16 h to obtain an aminated flame retardant.

[0045] Step 4: Add 20 g of aminated flame retardant, 5 g of urea and 5 g of dicyandiamide to 250 g of quartz fiber dispersion, stir and react at 45° C. for 24 hours to obtain a flame-retardant quartz fiber dispersion.

[0046] An aminated flame retardant rich in ammonium phosphate groups was prepared by the Mannich reaction, making full use of the primary amine, secondary amine and tertiary amine of polyethyleneimine. The aminated flame retardant was grafted onto the polymer chain grafted on the surface of quartz fiber through quaternization, so that the aminated flame retardant was evenly dispersed on the surface of quartz fiber.

[0047] Step 5. Dissolve 5 mL of tetramethyl orthosilicate in 30 mL of methanol in a beaker, mix with 250 g of flame-retardant quartz fiber dispersion, add 50 mL of 12 wt% 2-bromoethylamine hydrobromide ethanol solution, adjust the pH to 7 with ammonia water, stir the reaction at 55 ° C for 8 h, filter the solid, and wash the precipitate with ethanol and deionized water in turn to obtain a pretreated slurry.

[0048] By in-situ depositing nano-silica ions on the polymer chains on the surface of the quartz fiber, the aminated flame retardant is fixed on the surface of the quartz fiber through deposition, and nano-silica is introduced on the surface of the quartz fiber to improve the physical strength of the flame-retardant ceramic fiber felt.

[0049] Step six: filter the pretreated slurry in a mold at a low speed using a small-pore filter plate to form a fiber block, and then apply a pressure of 1.1 MPa to the fiber block to obtain a fiber wet blank. Dry the fiber wet blank in an oven at 65°C for 16 hours to obtain a flame-retardant ceramic fiber felt.

[0050] Comparative Example 1: The difference from Example 1 is that no polymer chain is added to the quartz fiber dispersion.

[0051] Comparative Example 2: The difference from Example 1 is that phosphorous acid is used to replace the aminated flame retardant.

[0052] Comparative Example 3: The difference from Example 1 is that the flame retardant quartz fiber dispersion is filtered and washed to replace the pre-treated slurry.

[0053] The sources of some reagents in the embodiments and comparative examples are as follows:

[0054] 2-(Dimethylamino)ethyl methacrylate, 2-(diisopropylamino)ethyl methacrylate, and tetramethyl orthosilicate were purchased from Sigma-Aldrich.

[0055] Azobisisobutyronitrile was purchased from Kaimart Chemical Technology Co., Ltd.

[0056] Polyethyleneimine was purchased from Shanghai Aladdin Reagent Co., Ltd.

[0057] Phosphorous acid, dicyandiamide and urea were purchased from Shanghai MacLean Biochemical Co., Ltd.

[0058] The diameter of quartz fiber is 3-5μm, the purity is 99.95%, and the density is 2.2g / cm 3 , purchased from Hubei Feilihua Quartz Glass Co., Ltd.

[0059] The flame retardant ceramic fiber felts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests. The sample size was 100 mm in diameter and 20 mm in height. According to the GBT17911-2018 standard, the tensile strength of the sample was tested. The flame retardancy of the material was tested by UL-94 and LOI. The results are shown in Table 1:

[0060] Table 1

[0061] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength / MPa 0.23 0.24 0.26 0.15 0.22 0.12 LOI / % 29.6 30.5 30.8 26.3 28.7 27.2 Flame retardant grade V-0 V-0 V-0 V-1 V-1 V-1

[0062] It can be seen from Table 1 that the flame-retardant ceramic fiber felts prepared in Examples 1 to 3 of the present invention have high tensile strength and good flame retardancy; since the surface of the quartz fiber in Comparative Example 1 is not modified by a polymer chain, the dispersibility of the quartz fiber in the aqueous solution is poor, the flame retardant cannot be dispersed on the surface of the quartz fiber, and the nano-silicon dioxide is unevenly deposited, resulting in low tensile strength and poor flame retardancy in Comparative Example 1; since the flame retardant in Comparative Example 2 is not aminated and modified, the degree of crosslinking between the flame retardant and the polymer chain is low and the dispersion is uneven, resulting in poor flame retardancy in Comparative Example 2; since nano-silicon dioxide particles are not deposited in the flame-retardant quartz fiber dispersion in Comparative Example 3, the tensile strength is poor, and there is no synergistic flame retardancy with the flame retardant, and the flame retardancy is poor.

[0063] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0064] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A production process for flame retardant ceramic fiber felt, characterized in that: The steps include: Step 1: Mix 2-(dimethylamino)ethyl methacrylate and 2-(diisopropylamino)ethyl methacrylate in tetrahydrofuran in a flask, add azobisisobutyronitrile, react at 65-75°C for 20-24h, cool and precipitate the solution with petroleum ether, and vacuum dry the obtained solid at 40-50°C for 36-48h to obtain a polymer chain; The pulped quartz fiber is mixed with distilled water, and the polymer chain is added. After stirring and dispersing, the pH value of the solution is adjusted to 3-4 with dilute sulfuric acid, ultrasonically dispersed for 30-40 minutes, and the pH value is adjusted to 6.5-7 with sodium hydroxide solution, and ultrasonically dispersed for 30-40 minutes to obtain a quartz fiber dispersion; Dissolve polyethyleneimine and phosphorous acid in deionized water in a beaker, drop formaldehyde into the beaker, react at 80-90° C. for 2-3 hours, adjust the pH value to 5-6 with ammonia water, remove the solvent by rotary evaporation, wash the solid with ethanol, and dry at 60-70° C. for 12-16 hours to obtain an aminated flame retardant; Adding aminated flame retardant, urea and dicyandiamide to the quartz fiber dispersion, stirring and reacting at 35-45° C. for 12-24 hours to obtain a flame retardant quartz fiber dispersion; Step 2: dissolve tetramethyl orthosilicate in methanol in a beaker, mix with the flame-retardant quartz fiber dispersion, add 10-12wt% 2-bromoethylamine hydrobromide ethanol solution, adjust the pH value to 6.5-7 with ammonia water, stir and react at 50-55°C for 6-8h, filter the solid, wash the precipitate with ethanol and deionized water in turn, and obtain a pretreated slurry; Step 3: Filter the pretreated slurry in a mold at a low speed using a small-pore filter plate to form a fiber block, and then apply a pressure of 1-1.1 MPa to the fiber block to obtain a fiber wet blank, and dry the fiber wet blank in an oven at 60-65° C. for 12-16 hours to obtain a flame-retardant ceramic fiber felt; The usage ratio of the quartz fiber, distilled water and polymer chain is 100-130 g: 1-1.5 L: 15-20 g; The dosage ratio of the polyethyleneimine, phosphorous acid, deionized water and formaldehyde is 10-15g:20-25g:100-120mL:20-25g; The usage ratio of 2-(dimethylamino)ethyl methacrylate, 2-(diisopropylamino)ethyl methacrylate, tetrahydrofuran and azobisisobutyronitrile is 2-3 g: 3-5 g: 80-100 mL: 6-8 mg.

2. The production process of a flame retardant ceramic fiber felt according to claim 1, characterized in that: The mass ratio of the quartz fiber dispersion, the aminated flame retardant, the urea and the dicyandiamide in step 1 is 200-250:15-20:3-5:3-5.

3. The production process of a flame retardant ceramic fiber felt according to claim 1, characterized in that: The dosage ratio of tetramethyl orthosilicate, methanol, flame-retardant quartz fiber dispersion and 2-bromoethylamine hydrobromide ethanol solution in step 2 is 4-5 mL: 20-30 mL: 200-250 g: 35-50 mL.

4. A flame retardant ceramic fiber felt, characterized in that: The invention is prepared by the production process described in any one of claims 1 to 3.